The Tettigoniidae (Orthoptera: Ensifera) from Ucumarí Regional Natural Park (RNP): Aspects of acoustical communication - MORRIS, GLENN K.; MONTEALEGRE-Z., FERNANDO (Revista Colombiana de Entomología, 2001)
Some aspects of acoustical communication of eight species of Tettigoniidae from Ucumarí Regional Natural Park (RNP) are presented for the first time. These specíes belong to three subfamilies: Pseudophyllinae (5 species): Trichottettix pilosula, Stetharasa exarmata, Chibchella nigrospecula, Scopioricus spatulatus, Typophyllum sp.; Copiphorinae (1 species): an unnamed genus and species, and Listroscelidinae (2 species): an unnamed genus and species. A brief diagnostic description and general ecological aspects of each species are provided. The physical structure of the five species found in Ucumarí is varied. The songs of the katydids described here are noisy, i.e. with many frequencies. The highest frequency encountered in this group was 17.5 kHz, produced by T. pilosula, and the lowest was 8 kHz, produced by Scopioricus spatulatus. Only one species presented energy in the ultrasonic range, and three species produced a band spectrum: Chibchella nigrospecula, Stetharasa exarmata, and Scopioricus spatulatus; all of the others tend toward high-Q tones.